2021
DOI: 10.1007/jhep03(2021)022
|View full text |Cite
|
Sign up to set email alerts
|

On p-form gauge theories and their conformal limits

Abstract: Relations between the various formulations of nonlinear p-form electrodynamics with conformal-invariant weak-field and strong-field limits are clarified, with a focus on duality invariant (2n − 1)-form electrodynamics and chiral 2n-form electrodynamics in Minkowski spacetime of dimension D = 4n and D = 4n + 2, respectively. We exhibit a new family of chiral 2-form electrodynamics in D = 6 for which these limits exhaust the possibilities for conformal invariance; the weak-field limit is related by dimensional r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 69 publications
1
80
0
Order By: Relevance
“…We should remark here that the coupling of generic nonlinear four-dimensional conformal electrodynamics theories to gravity has been investigated in [6], where it was shown that a certain condition on black hole charges restricts the form of any conformal electrodynamics Lagrangian to a particular one-parameter extension of the Maxwell case. As we observed in [5], this class of conformal electrodynamics includes (after a constant rescaling of the gauge potential A m ) the conformal and duality-invariant ModMax theory. More recently, investigations similar to those of [6] but specific to ModMax have been carried out and further extended in [7][8][9][10] (see also [11][12][13]).…”
Section: Jhep10(2021)031mentioning
confidence: 60%
See 2 more Smart Citations
“…We should remark here that the coupling of generic nonlinear four-dimensional conformal electrodynamics theories to gravity has been investigated in [6], where it was shown that a certain condition on black hole charges restricts the form of any conformal electrodynamics Lagrangian to a particular one-parameter extension of the Maxwell case. As we observed in [5], this class of conformal electrodynamics includes (after a constant rescaling of the gauge potential A m ) the conformal and duality-invariant ModMax theory. More recently, investigations similar to those of [6] but specific to ModMax have been carried out and further extended in [7][8][9][10] (see also [11][12][13]).…”
Section: Jhep10(2021)031mentioning
confidence: 60%
“…It was also shown in [1] that ModMax electrodynamics is the weak-field limit of a oneparameter duality-invariant generalization of Born-Infeld (BI) electrodynamics, although only the Hamiltonian density of this BI-like theory was found there. The corresponding Lagrangian density is [5] L (γBI) = T − T 2 − 2T (cosh γ)S + (sinh γ) S 2 + P 2 − P 2 , (1.3) where T is the BI constant with dimensions of energy density; for γ = 0 we recover the BI theory for which T can be interpreted (in a string-theory context) as the D3-brane tension. The Lagrangian density of (1.1) is recovered in the T → ∞ limit, which is equivalent to a weak-field limit.…”
Section: Jhep10(2021)031mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, for the 6D chiral 2-form theories there is exactly the same number "two" of independent Lorentz-invariants as in D = 4 (e.g. like P 1 and P 2 in this paper) which can be used to construct their consistent non-linear generalizations, which are always related to those in 4D theory [47].…”
Section: Jhep04(2021)187mentioning
confidence: 91%
“…It has been shown in ref. [47] that in 6D there is a unique non-linear conformal modification of the free chiral 2-form theory which is related to a non-linear modification of 4D Maxwell electrodynamics by dimensional reduction (see also [59]). It would be of interest to investigate the TT deformation for a 6D non-linear theory of the so-called chiral 2-forms whose 3-form field strength satisfies a self-duality condition.…”
Section: Jhep04(2021)187mentioning
confidence: 99%